The occupational structure of rural workers in Mathura district, UttarPradesh - Kaushik, Kapil; Kaushik, Ashok Kumar (National Geographical Journal of India, 2021)
Occupational structure refers to the division of workers into different types of economic activities. It is the activities by which people secure their livelihood and it also provides background knowledge for formulating development plans for any region. The paper presents the occupational structure of rural workers in the Mathura district. Mathura district is situated in the western part of Uttar Pradesh and has a high religious and economic importance. The whole study is mainly based on primary data collected through a structured interview schedule designed for the purpose. Field surveys were conducted during 2015-16 and 5270 respondents (2929 males and 2341 females) of 755 households were questioned to generate primary data. In the surveyed villages, the share of cultivators and agricultural labourers was 44.41 % and 16.32 % respectively. So a large share of workers was engaged in primacy activities (66.73%). The analysis shows that there is a negative relation between workers and literacy rate. It happens because as people get employment in cities they leave the village and only unemployed literates stay there. The results were derived with the help of statistical techniques and SPSS software whereas maps were prepared with the help of GIS Arc View software.